Developing a Research Agenda Towards Patient Centered Care for Epilepsy in Nepal - Shrestha, Swastika; Rajbhandari, Hemav; Dhital, Raghu; Caws, Maxine (Annapurna Journal of Health Sciences, 2026)
Background & Method: There are substantial knowledge, and evidence gaps regarding epilepsy in Nepal which prevent progress towards patient centered care provision.A workshop was conducted in Kathmandu, Nepal where we brought together multidisciplinary stakeholders involved in epilepsy care for a participatory discussion. The workshop aimed to identify the landscape of existing psychosocial and medical support available for people living with epilepsy in Nepal and prioritize research topics related to care service provision, access and delivery to inform the design of future research.Results: The workshop identified important research topics which were grouped into three major themes: Stigma; Epidemiological studies; and Access to Medicine/Services/Support. Based on the workshop discussion, we have proposed a priority research agenda to inform development of models of person-centered epilepsy care in Nepal.Conclusions: Our workshop highlighted the dearth of information regarding all aspects of epilepsy in Nepal, and the urgent need for intersectoral knowledge exchange.